2017
DOI: 10.1016/j.hfc.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-oncology Related to Heart Failure

Abstract: Summary There are many similar risk factors for both cancer and cardiovascular disease. There are substantial biological data to support the hypotheses that the pathogenesis of these 2 diseases overlaps. Exercise should be strongly encouraged and should continue to be a focus of ongoing research. The management of risk factors for cardiovascular disease and cancer, including tobacco use, a healthy diet, and normal weight, should be further addressed. Treatment of cardiac risk factors, including hypertension, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 122 publications
(118 reference statements)
1
24
0
1
Order By: Relevance
“…Annually, about 18 million of people die from CVD [2], while, in 2018, there were 18 million new cases of cancer and approximately 10 million cases of cancer deaths worldwide [1,3]. These disorders share not only this disgraceful leadership—they are also intrinsically linked via common risk factors, chronic inflammatory states and cardiac and vascular toxicities of chemo and radiotherapy [4,5,6]. Recently, Venneri et al indicated that oncological patients who have not received any therapy may be endangered by CVD, as a growing mammary tumor may itself have a deleterious effect on the heart [7].…”
Section: Introductionmentioning
confidence: 99%
“…Annually, about 18 million of people die from CVD [2], while, in 2018, there were 18 million new cases of cancer and approximately 10 million cases of cancer deaths worldwide [1,3]. These disorders share not only this disgraceful leadership—they are also intrinsically linked via common risk factors, chronic inflammatory states and cardiac and vascular toxicities of chemo and radiotherapy [4,5,6]. Recently, Venneri et al indicated that oncological patients who have not received any therapy may be endangered by CVD, as a growing mammary tumor may itself have a deleterious effect on the heart [7].…”
Section: Introductionmentioning
confidence: 99%
“…Making use of the PONS study cohort, the association of select, lifestyle-related factors with cancer-specific and non- cancer-specific mortality was assessed. Considering that the same lifestyle-related factors, e.g., obesity, smoking, alcohol, dietary intake of red meat, and low level physical activity, are the acknowledged risk factors for both cancer and non-cancer death (e.g., fatal CVDs), making use of the statistical methods which take due account of the competing risks has deliberately been opted for (8,9). To this end, two statistical methods were applied, i.e., CSH and SHR, which make it possible to pursue the analyses which take into account the presence of more than one end-event.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the enumerated factors may effectively be controlled through a modification of individual lifestyle (7). It is well-worth highlighting at this juncture that all cancer-related or cardiovascular events with either fatal, or non-fatal outcomes are similar to some extent (8,9). Population aging process contributes to an increased incidence of cancer-and noncancer-specific deaths, quite similar when accompanied by identical, common risk factors (10).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is an increasing amount of evidence that cancer and CVD share not only the risk factors but also the mechanism of pathogenicity [4,5]. This is confirmed mainly in the case of breast cancer by the increased cardiac risk in patients receiving chemotherapy and radiotherapy as well as in cancer survivors [6][7][8][9][10]. It is also plausible that cancer itself may deleteriously affect heart function, irrespective of exposure to anticancerogenic therapies.…”
Section: Introductionmentioning
confidence: 99%